Gain- and loss-of-function of Rhp51, a Rad51 homolog in fission yeast, reveals dissimilarities in chromosome integrity - Kim, Woo Jae (Oxford University Press, 2001)
Rad51 is crucial not only in homologous recombination and recombinational repair but also in normal cellular growth. To address the role of Rad51 in normal cell growth we investigated morphological changes of cells after overexpression of wild-type and a dominant negative form of Rad51 in fission yeast. Rhp51, a Rad51 homolog in Schizosaccharomyces pombe, has a highly conserved ATP-binding motif. Rhp51 K155A, which has a single substitution in this motif, failed to rescue hypersensitivity of a rhp51Δ mutant to methyl methanesulfonate (MMS) and UV, whereas it binds normally to Rhp51 and Rad22, a Rad52 homolog. Two distinct cellular phenotypes were observed when Rhp51 or Rhp51 K155A was overexpressed in normal cells. Overexpression of Rhp51 caused lethality in the absence of DNA-damaging agents, with acquisition of a cell cycle mutant phenotype and accumulation of a 1C DNA population. On the other hand, overexpression of Rhp51 K155A led to a delay in G(2) with decondensed nuclei, which resembled the phenotype of rhp51Δ. The latter also exhibited MMS and UV sensitivity, indicating that Rhp51 K155A has a dominant negative effect. These results suggest an association between DNA replication and Rad51 function.